Large-scale prion protein genotyping in Canadian caribou populations and potential impact on chronic wasting disease susceptibility - Arifin, M.I. (Maria Immaculata); Staskevicius, A. (Antanas); Shim, S.Y. (Su Yeon); Huang, Y.-H. (Yuan-Hung); Fenton, H. (Heather); McLoughlin, P.D. (Philip D.); Mitchell, G. (Gordon); Cullingham, (Catherine); Gilch, S. (Sabine) (Molecular Ecology, 2020)
Polymorphisms within the prion protein gene (Prnp) are an intrinsic factor that can modulate chronic wasting disease (CWD) pathogenesis in cervids. Although wild European reindeer (Rangifer tarandus tarandus) were infected with CWD, as yet there have been no reports of the disease in North American caribou (R. tarandus spp.). Previous Prnp genotyping studies on approximately 200 caribou revealed single nucleotide polymorphisms (SNPs) at codons 2 (V/M), 129 (G/S), 138 (S/N), 146 (N/n) and 169 (V/M). The impact of these polymorphisms on CWD transmission is mostly unknown, except for codon 138. Reindeer carrying at least one allele encoding for asparagine (138NN or 138SN) are less susceptible to clinical CWD upon infection by natural routes, with the majority of prions limited to extraneural tissues. We sequenced the Prnp coding region of two caribou subspecies (n = 986) from British Columbi